2005
DOI: 10.1098/rsif.2004.0020
|View full text |Cite
|
Sign up to set email alerts
|

Roles of discontinuities in bio-inspired adhesive pads

Abstract: Morphological intricacies of the biological attachment pads generate considerable interest owing to their remarkable ability to control adhesion to various surfaces. Motivated by the adhesive microstructures of insects, we examine the behaviour of adhesion and crack propagation in patterned adhesive films. These films are made of silicone elastomers that were patterned with lateral, longitudinal or crosswise incisions from which a thin silanized glass plate was removed in a displacement-controlled peel experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
163
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 21 publications
4
163
1
Order By: Relevance
“…Note in Fig. 5B that voids do in fact nucleate ahead of the opening crack tip in several instances, as is the case with thin soft films in confined geometry (40,41). Failure by void nucleation represents the maximum enhancement possible by the mechanism proposed here and is limited by individual fibril detachments, a situation that has been studied in detail elsewhere (21,30).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Note in Fig. 5B that voids do in fact nucleate ahead of the opening crack tip in several instances, as is the case with thin soft films in confined geometry (40,41). Failure by void nucleation represents the maximum enhancement possible by the mechanism proposed here and is limited by individual fibril detachments, a situation that has been studied in detail elsewhere (21,30).…”
Section: Resultsmentioning
confidence: 90%
“…Failure by void nucleation represents the maximum enhancement possible by the mechanism proposed here and is limited by individual fibril detachments, a situation that has been studied in detail elsewhere (21,30). Before concluding, it should be noted that crack arrest and re-initiation have been observed to enhance adhesion, even in nonfibrillar systems (40)(41)(42)(43). These cases involve incisions in thin confined films (40,41), discontinuity of film thickness (42,43), and the discontinuity of the elastic modulii of adjoining films (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of adhesive tapes, Kendall has shown that the peeling strength of tapes with patches of different stiffness or thickness can be much higher than the tapes with uniform thickness and stiffness (16). Chaudhury and coworkers have shown that 100-to 200-m patches on poly(dimethylsiloxane) sheets increases the peeling force by a factor of 10-20 in comparison to a unpatterned poly(dimethylsiloxane) sheet (17). We postulate that the mechanism in all of these cases, including the patterned gecko tape, is to stop, deviate, and reinitiate the crack propagation in comparison to materials with uniform properties (also referred to as the Cook-Gordon mechanism) (15).…”
Section: Resultsmentioning
confidence: 99%
“…Recent interest in bio-inspired adhesives has motivated many researchers to fabricate microfibril arrays (Liu & Bhushan 2003;Peressadko & Gorb 2004;Chung & Chaudhury 2005;Crosby et al 2005;Glassmaker et al 2005Glassmaker et al , 2007Huber et al 2005;Northen & Turner 2005;Yurdumakan et al 2005;Kim & Sitti 2006;Majidi et al 2006;Aksak et al 2007;Gorb et al 2007;Greiner et al 2007; and to study their contact mechanics and adhesion (Jagota & Bennison 2002;Gao et al 2003Gao et al , 2005Persson & Gorb 2003;Hui et al 2004;Persson et al 2005;Spolenak et al 2005a,b;Tang et al 2005;Bhushan et al 2006;Tian et al 2006;Yao & Gao 2006;Chen & Gao 2007). Most of these studies focus on how the interface between the microfibrils and a smooth, hard substrate separates under a normal load.…”
Section: Introductionmentioning
confidence: 99%